A Diastereoselective Synthetic Approach towards the Synthesis of Berkeleylactone F and Its 4-epi-Derivative - Subba, Srijana; Saha, Sumit; Mandal, Susanta (SynOpen, 2020)
A diastereoselective approach to the synthesis of berkeleylactone F is presented. The synthetic strategy is initiated with commercially available (R)-glycidol, 1,6-heptadiyne, and (R)-(+)-methyl lactate. The key feature of the approach is directional functionalization at both terminals of 1,6-heptadiyne.
Keywords: macrolide; epoxide; ring opening; heptadiyne